An In-depth Analysis of Assessment Design: Alignment between Baluchistan English Language Textbooks and Pakistan National Curriculum - Kakar, Zia Ul Haq; Kaukab, Syeda Rakhshanda (Pakistan Journal of Humanities and Social Sciences, 2023)
Textbooks are the learning and assessment materials developed on the curriculum. It provides practical opportunities for the implementation of the assessment design of the curriculum. This study examines the alignment between the assessment design in Pakistan's English language curriculum and Baluchistan’s English language textbooks of secondary classes. It explores the levels of assessment design envisioned in students' learning outcomes, exercises, strategies, and guidelines in textbooks. The document analysis strategy is applied to Baluchistan’s English language textbooks for secondary classes using Bowen's (2009) procedure. The results show that textbooks cover all SLOs envisioned in Pakistan's national curriculum. The SLOs are poorly clustered for lessons, causing low assessment design and ultimately affecting assessment practices. Most of the assessment strategies were developed on Bloom’s taxonomy cognitive domain lower level indicated the low assessment design. The weightage and significance for developing assessment strategies were mostly given to "Grammar" and, to some extent, “Writing” competencies. Fewer strategies were developed for “Reading Comprehension and Thinking” Skill competency. "Oral communication" competency is nearly overlooked, and listening skills are completely ignored. Teachers' and students' guidelines regarding assessment are completely missing in textbooks.